Analisa Pajak Daerah, Retribusi Daerah, Dana Perimbangan Serta Pengaruhnya Terhadap Belanja Modal (Studi Kasus Pada Pemerintah Daerah Kabupaten/Kota Di Provinsi Jawa Tengah Tahun 2016-2018) - LMS Kristiyanti; Maya Widyana Dewi (ITB AAS INDONESIA, 2021)
The study aims of this the effect of Local Taxes, Local Retributions and Balanced Funds to the Capital Expenditures on Regency and Municipal Government Central Java Province year 2016-2018. The research is a quantitative research. The subject of the research are regency and Municipal Government in Central Java Province with total 35 regencies and municipalities. Data used comes from the 2016-2018 Regional Revenue Budget Realization Report . The technique of collecting data using documention method. The test of prerequisite analysis using classical assumption test, those are normality, multicolinearity, heteroscedasticity and autocorrelation. The hypoyhesis test in this study used multiple linier regression analysis, t test (partial), F test (simultaneous) and coefficient of determination (R2). The results of this reseach showed that partially the Regional Tax variable and the Balance Fund has a significant effect on capital expenditure. Regional levies variable does not significantly influence capital expenditure. Simultaneously, Regional Tax, Regional Retribution, and Balancing Funds have a significant effect on capital expenditure. The influence of these three variables on Capital Expenditures on Regency is 68.9% while the remaining 31.1% was influenced by other variables besides the variables used in this study. So it can be concluded that if the Regional Tax and Balance Fund increase, it will increase the allocation of Capital Expenditures. While Regional Retribution is not significant due to the lack of optimal excavation, management of resources owned by the government of Central Java Province to be able to increase the Original Regional Revenue. Keywords: Balance Funds, Capital Expenditures, Local Tax, Local Retribution